Soft templated mesoporous carbons: Tuning the porosity for the adsorption of large organic pollutants - Libbrecht, Wannes; Verberckmoes, An; Thybaut, Joris W.; Van Der Voort, Pascal; De Clercq, Jeriffa (Carbon (New York), 2017)
Mesoporous carbons have been the subject of various studies, both fundamental and applied. Fundamental studies revealed numerous synthesis routes which can adjust material characteristics as specific surface area, pore volume, pore size or morphology and elemental composition. The indirect synthesis or hard template method was developed first. An extensive collection of template materials exist, which can be impregnated with carbon precursors to provide various hard templated mesoporous carbons with a precise control of mesoporosity and pore geometry. However, the more recent direct method or soft template method offers some specific advantages. By using the organic-organic self-assembly between polymerizable precursors and block copolymer surfactants as structure directing agents it is possible to obtain tunable morphology and surface properties, mechanical stability and reduce the number of synthesis steps, thereby decreasing synthesis cost and complexity. Applied studies valorize this wide variety of mesoporous carbons. Fine-tuning material characteristics as surface area, pore volume, pore size, morphology, chemical composition or possible post-modification or nanoparticle doping give rise to applications in catalysis, electrochemistry, energy storage, separation or adsorption. In adsorption, mesoporous carbons are considered as a new family of adsorbents challenging the well-known activated carbon by introducing the advantage of increasing pore size. This allows mesoporous carbons to adsorb larger molecules and enhance the adsorption kinetics. In this review we present the most recent achievements and advances in the synthesis of soft templated mesoporous carbons, with focus on pore size control, and their potential as a new family of carbon adsorbents.